Tingkat Kesukaan Konsumen Terhadap Flavor Alami Daun Pandan (Pandanus Amaryllifolius) dan Daun Jeruk Purut (Citrus Hystrix) pada Nata De Coco - Ramadan, Ramadan; Pratama, Muhammad Doddy; Purbawati, Purbawati (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Utilization of old coconut water waste can be used as an economical product such as nata de coco. Testing the level of consumer preference for nata de coco is not only seen from the chemical aspect but also from the color, texture, scent and taste. This study aims to determine the level of consumer preference for nata de coco which is given a natural flavor from pandan leaves and kaffir lime leaves in nata de coco by using organoleptic assay. The results were analyzed by one-way ANOVA and showed by average calculation. The results of the (hedonic) organoleptic test showed that for color and texture, consumer preferred pandan leaves were better than kaffir lime leaves as natural flavour. Meanwhile, the scent and taste of Citrus leaves were better compared to pandan leaves.